2019
DOI: 10.1039/c9ra05285b
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and efficient sugar production from wheat straw by pretreatment with biogas digestate

Abstract: The effect of wheat straw pretreatment with hot water and liquid fraction of biogas digestate was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…Figure 1D shows that initial uniform and rigid structure of the WS was changed after pretreatment, obtaining a porous structure which can positively influence the enzymatic action. This modification has also been reported by Zheng et al (2018) and Momayez et al (2019) [24,54].…”
Section: Scanning Electron Microscope (Sem) Analysissupporting
confidence: 85%
“…Figure 1D shows that initial uniform and rigid structure of the WS was changed after pretreatment, obtaining a porous structure which can positively influence the enzymatic action. This modification has also been reported by Zheng et al (2018) and Momayez et al (2019) [24,54].…”
Section: Scanning Electron Microscope (Sem) Analysissupporting
confidence: 85%
“…These are the compounds that are most easily solubilized in this type of hydrothermal pretreatment, since their structure is less complex than that of other components of the vegetable waste [ 41 , 49 , 51 , 63 , 64 , 65 ]. The decrease in the solid recovery was well in agreement with the literature [ 35 , 66 , 67 , 68 , 69 ]. Additionally, the low values (always lower than 55%) may be explained by the easy solubilization and volatilization phenomena of certain compounds, as previously described by Mok and Antal [ 64 ].…”
Section: Resultssupporting
confidence: 92%
“…While untreated wheat straw shows an organized and compact structure, the surface of steam-exploded wheat straw became scattered and porous, due to the destruction of the lignincellulose-hemicellulose complex's integrity. Other authors observed similar changes in wheat straw's morphology and structure caused by various pretreatments when imaging with a scanning electron microscope [24,53]. Due to significantly lower amounts of sugars and, hence, limited suitability for yeast growth experiments, as shown in Fig.…”
Section: Discussionmentioning
confidence: 57%